2015
DOI: 10.1089/ten.teb.2014.0383
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Substrate Mechanics on Cardiomyocyte Maturation and Growth

Abstract: Cardiac tissue engineering constructs are a promising therapeutic treatment for myocardial infarction, which is one of the leading causes of death. In order to further advance the development and regeneration of engineered cardiac tissues using biomaterial platforms, it is important to have a complete overview of the effects that substrates have on cardiomyocyte (CM) morphology and function. This article summarizes recent studies that investigate the effect of mechanical cues on the CM differentiation, maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 47 publications
5
73
0
1
Order By: Relevance
“…An ideal cardiac model should accurately recapitulate the physiology of natural heart, which is a difficult task due to the complex structure and function of the human heart. In past studies, intensive efforts have been made to develop various kinds of scaffolds that mimic the architecture and biophysics of native heart, for example, modulating the electrical conductivity, mechanical stimulation,[4a,23] and anisotropic properties of the scaffolds. These scaffolds could partially enhance the cardiac cell attachment/alignment; facilitate electrical signal propagation and cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal cardiac model should accurately recapitulate the physiology of natural heart, which is a difficult task due to the complex structure and function of the human heart. In past studies, intensive efforts have been made to develop various kinds of scaffolds that mimic the architecture and biophysics of native heart, for example, modulating the electrical conductivity, mechanical stimulation,[4a,23] and anisotropic properties of the scaffolds. These scaffolds could partially enhance the cardiac cell attachment/alignment; facilitate electrical signal propagation and cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have found similar relationships between substrate stress, cardiomyocyte calcium levels, and force generation, as reviewed in [5]. Using cardiomyocytes from quail chick embryos, one study found that the spontaneous beating frequency, as well as the percentage of beating cells, increased as the stiffness of the underlying substrate decreased ([6]).…”
Section: Introductionmentioning
confidence: 91%
“…The above-mentioned methods have also been used to elucidate the role of mechanical signaling in hypertrophic signaling in both a physiological and pathological context [208,209]. In this section, a review of the relevant literature focuses on efforts to enhance CM function and phenotype via mechanical stimulation as well as studies aimed at utilizing mechanical stimulation as a tool to understand hypertrophic signaling in CMs (Note: for a more complete review, see Zimmermann et al in this issue or Tallawi et al [210]).…”
Section: Mechanical Stimulation Of Cardiac Cells and Tissuesmentioning
confidence: 99%